2021
DOI: 10.1021/acs.macromol.0c02801
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Weight on Viscosity Scaling and Ion Transport in Linear Polymerized Ionic Liquids

Abstract: A series of acrylic polymerized ionic liquids (PILs) with imidazolium cations and bis­(trifluoromethylsulfonyl)­imide (TFSI) anions were synthesized via reversible addition–fragmentation chain-transfer polymerization. The absolute molecular weights (MWs) of PILs were determined from size exclusion chromatography with light scattering. The degree of polymerization (N) ranged from 15 to 254, and steady rotational rheology indicated the zero-shear viscosity (η0) measured at a constant distance above the glass tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 62 publications
8
25
2
Order By: Relevance
“…Ionic repulsive interactions strongly affects (induce significant increase) of the glass transition temperature of low and high molecular weight soft materials. Such a behavior was already reported for linear poly(ionic liquids) [69]. Therefore, one can suppose that along with increasing concentration of DMAEMA the number of ionic interactions gets lower leading to the depression of the T g [70].…”
Section: Resultssupporting
confidence: 71%
“…Ionic repulsive interactions strongly affects (induce significant increase) of the glass transition temperature of low and high molecular weight soft materials. Such a behavior was already reported for linear poly(ionic liquids) [69]. Therefore, one can suppose that along with increasing concentration of DMAEMA the number of ionic interactions gets lower leading to the depression of the T g [70].…”
Section: Resultssupporting
confidence: 71%
“…The conditions for ion exchange were shown to be sufficient in prior work, and the elemental analysis confirmed that the residual bromide contents for the four PILs were < 0.7 wt % (Table S1). The Im TFSI PIL sample with a number-average degree of polymerization determined by nuclear magnetic resonance ( N NMR ) of 290 was used from the previous study . The Im BF 4 PIL was synthesized from a separate batch of Br PIL with N NMR = 110 (Figure S1a).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the bromo-terminated acrylate, the imidazolium Br ionic liquid monomer and the Im Br PIL were previously reported by our group and used without any modification. 1…”
Section: Synthesis Of 3-bromopropyl Acrylate 1-(3-(acryloyloxy)propyl)-3-methyl-imidazolium Bromide (Im Br Il) and Poly(1-(3-(acryloyloxymentioning
confidence: 99%
“…The Im TFSI PIL with N NMR =290 was used from previous work. 1 The Im BF 4 PIL was prepared by ion exchange. Im Br PIL (0.198 g, 0.72 mmol Br -) was dissolved in 10mL DI water and added dropwise to a solution of NaBF 4 (0.79g, 7.2 mmol BF 4 -) in 10mL DI water in a 1kDa MWCO dialysis bag.…”
Section: Synthesis Of Im Tfsi Pilmentioning
confidence: 99%
See 1 more Smart Citation